PERANCANGAN MODUL DATA AKUISISI PENGATURAN KECEPATAN MOTOR DC DENGAN MASUKAN DAC MENGGUNAKAN MATLAB - Abdul Hafid (VERTEX ELEKTRO, 2020)
This study aims to: (1) To Set the DC motor rotation with input DAC using Matlab, (2) To produce a data acquisition system with a portable hardware. The tools are designed in the form of a regulator and a DC motor drive with DAC input that can slow down and brought forward in accordance with the input value by utilizing PPI matlab program as a means of sending control signals to the DAC as a digital signal converter to analog signals. The software has been created in order pendekode decoding process runs efficiently when multiple application programs to access the system simultaneously. To allow users to access the system, the script code application program interface has been made in matlab language. The results of this study indicate that PPI and DAC capable of acquiring the data input mode minimum 60 bits (00.1111 million and 1.5625 volts) with a speed of 1066.41 rpm and a maximum input of 255 bits (11111111 and 4.9 Volt) with a speed of 922.852 rpm